Examination of the Prediction of Person-Job Fit on Person-Organization Fit from the Perspective of Academics - Sermin Ağrali Ermiş,; Ünsal Altinişik,; Gül Eda Burmaoğlu, (Journal of Educational Issues, 2024)
Educational institutions show their activities in an intense environment and lead the generations that will be the architects of the future. Considering the importance of education, it is important for academics to transfer their knowledge and experience to students by blending them with scientific data in this intense environment. However, in order for educational process to work efficiently, it is thought that the harmony of the person with his job and organization is the main point to be emphasized. In this context, this research aimed to determine the person-organization and Person-Job Fit of academics, to determine the relationship between these two variables, and to determine the predictive role of person-to-job fit on Person-Organization Fit working in the field of education. In this study, which was carried out in the relational screening model, the opinions of 403 academics were taken voluntarily. The “Personal Information Form” created by the researchers as a data collection tool in the research, and the “Person-Organization Fit Scale” developed by Netemeyer et al. (1997) and adapted to Turkish culture by Turunç and Çelik (2012) to measure the Person-Organization Fit and “Perceived Person-Job Fit Scale”, adapted to Turkish culture by Yaşar (2009) by benefiting from the researches of Cable and Judge (1996) and Saks and Ashforth (1997) was used to measure perceived Person-Job Fit. As a result of the analyzes made; It has been seen that there is a positive relationship between Person-Organization Fit and Person-Job Fit, and Person-Job Fit is a predictor of Person-Organization Fit. In addition, it was determined that the person-to-work and Person-Organization Fit of the academics were above the medium level. When the scale of Person-Organization Fit is examined, there is no difference in terms of gender, academic title and department of duty, but a significant relationship has been determined according to marital status. When the Person-Job Fit Scale was examined, it was determined that there was no relationship according to gender and the department, and there was a significant difference according to marital status and academic title.